(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Critical thinking has become one of the most important skills in twenty-first century education. In English language teaching (ELT), critical thinking enables learners to analyze information, evaluate arguments, solve problems, and express their ideas effectively. This article examines the role of critical thinking in English language learning and discusses practical ways teachers can foster critical thinking skills in the classroom.